MENINGKATKAN KETERAMPILAN KOLABORASI PESERTA DIDIK SDN 181/IV KOTA JAMBI MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Suci Afnitri Wahyuni; Maryono; Meliwati; Sri Wahyuningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The ability to collaborate is key to 21st century competencies because today's education emphasizes 4K. The 4K is are collaboration, creativity, critical thinking and communication. However, in Indonesia, collaboration skills are often not well improved compared to other competencies. This research is classroom action research (CAR) using the Suharsimi Arikunto model. The process is cyclical, with each cycle consisting of two meetings, each lasting 2 x 35 minutes. Each cycle includes four stages: (1) action planning, (2) implementation, (3) observation, and (4) reflection. Data was collected through observation during learning and using a collaborative observation rubric. The research results show that the Problem Based Learning (PBL) model is effective in improving collaborative skills. Initially students had low collaborative skills, but after two PBL cycles, there was a significant increase with all collaborative indicators being met. These collaborative indicators are positive interdependence, face-to-face interaction, personal responsibility, communication skills, and group work. The PBL model has proven to be effective in improving students' collaborative skills. Keywords: collaboration skills, elementary education, learning models